KOMPLEKSITAS MASALAH PEKERJA ANAK DI INDONESIA - Ahmad Sofian (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
Children workers are complex problems. On one side, they must work because of poverty, and on another side, they mostly do not get government's protection. Case of Jermal children workers along east sea shore of North Sumatra shows that they are susceptible to exploitation. Some risks they have to face are: high risk of weather and wave of the sea, cruel treatment, forced labour, unguaranteed job s avety and threat of death. The writer of this matter indicates that at least there are three kinds of violations, namely 1) that of human rights,2) that of labour law and 3) that of creation of broken society against social system.